Analysis of Regional Expenditure Performance in the Report Budget Realization in Planning Agency Regional (BAPEDA) Majene District: Case study of Regional Planning Board of Majene Regency - Rusnah (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the expenditure performance of the District Planning Agency. Majene in the Budget Realization Report regarding the difference between spending and the budget, spending growth, spending efficiency and how capital expenditures and operations are being carried out. This research is a quantitative descriptive study, the data used is secondary data in the form of a report on the realization of the Regional Planning Agency's budget for the 2018-2020 fiscal year in Kab. Majene. The analytical techniques used are analysis of spending variance, analysis of spending growth, analysis of spending efficiency, and shopping compatibility. The results of this study indicate that the results of the analysis of the expenditure variance in 2018 - 2020 expenditure performance are considered good even though in 2018 the level of budget realization is very low, which is only 22% compared to the following year. Analysis of spending growth in 2018 – 2019 increased by 362%. Meanwhile, in 2019-2020, it actually decreased by 37% percent from last year. Expenditure efficiency analysis in 2018 the level of budget efficiency is 22%, in 2019 the level of budget efficiency is 98%, and in 2020 the level of budget efficiency is 95%. Although in 2018 the level of budget efficiency is still relatively good because it does not exceed the total budget target or the level of budget efficiency is above 100%. The compatibility analysis, namely the analysis of capital expenditures on total expenditures, shows that in 2018 the level of capital expenditure was only 1%, in 2019 it was only 2% and in 2020 it was only 1%. As for the analysis of operating expenses in 2018 it was 99%, in 2019 it was 98%, and in 2020 it was 99%.